Managing knowledge risks in intrapreneurial environment - Adrian Dumitru Tanţău; Eliza Laura Paicu (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The knowledge-based view of the firm argues that knowledge and the capability to create and share it are the key resource of the firm's competitive advantage. Since many organizations are becoming knowledge intensive, an increased need of awareness regarding the risks residing in the knowledge processes develops, as well as the need to know how these risks affect the entrepreneurial behavior of people inside the company. In this paper we seek to provide a structured framework of knowledge risks, based on relevant literature and results of semi-structured interviews conducted with middle managers inside ten banking institutions. Using the Delphi method, we also explore whether effective management of knowledge risks boosts the entrepreneurial skills of employees working in a bank, thus fostering intrapreneurship. Our qualitative research provided us with a much needed classification framework of knowledge risks, molded on the classic configuration of the knowledge processes. Moreover, we have validated the knowledge variables which highly influence the intrapreneurial environment in a bank. We contribute to the scarce literature written on the topic of knowledge risks, by identifying the critical knowledge risk drivers and we detail how managing these risks can enhance the competitiveness of the firm. The research led us to discover that the most powerful variable residing in the knowledge processes flow is collaboration and communication among the actors involved.
Keywords: 650; communication and collaboration; intrapreneurship; knowledge risks; knowledge sharing; organizational culture